The Authority of A Notary Who Is Declared Bankrupt Against The Validity of The Deed That Has Been Made - Savarina, Anitya Arwa; Badriyah, Siti Malikhatun (Postgraduate Program in Law, Pattimura University, 2025)
Introduction: Notaries have the authority to make authentic deeds based on the Notary Law. However, if a notary is declared bankrupt, a statement will arise regarding his/her authority and the validity of the deeds that have been made. However, deeds made before the notary goes bankrupt remain valid as long as they meet the legal requirements.Purposes of the Research: This study aims to explore the legal impact and responsibilities of notaries who are declared bankrupt, especially regarding the validity of the documents they have created.Methods of the Research: The type of research used is Normative Juridical research or library legal research method, namely reviewing laws and regulations and relevant case studies on the importance of understanding bankruptcy status where notaries affect their professional duties and the authenticity of legal documents.Results Main Findings of the Research: The results show that deeds made by a notary before being declared bankrupt generally still have legal validity, although bankruptcy can affect public trust and the notary's ongoing responsibility.